Three essays on perceived relative financial status and well-being in older adults - Clady, Joy P. (Kansas State University, 2020)
In three studies, this dissertation explores the potential connection between financial perceptions, comparisons, and various components of well-being in older adults. Together, the studies aim to add to our understanding of the importance of subjective financial measures, comparisons to others, enduring effects of childhood financial status perceptions, and perceived relative financial changes over time. Such inquiry adds to our understanding of a piece of the pathway to well-being and successful aging. Each study relies on a distinct theoretical perspective, with each including or accommodating the concepts of perceptions and comparisons. The ubiquitousness of these concepts among different theories points to these themes’ importance. Data were obtained from Waves 2 and 3 of the National Social Life, Health, and Aging Project (Waite et al., 2013). Essay One used an Ordinary Least Squares (OLS) regression to investigate the relationship between perceived relative income and happiness, as indicated by symbolic interactionism and its subtheory, reference group theory (Merton, 1968). The study also aimed to evaluate who were more salient referent others – American families in general, or peers. Using a sample of 2,101 older adults, the study did not find statistical support for the connection between either the national or the peer-based perceived relative income and happiness, and no determination could be made as to which referent other was more influential on individual happiness. Essay Two examined the relationship between recalled perceived family financial status during childhood and anxiety in older adults through the lens of life course perspective, which holds that childhood experiences, particularly those that occur during critical periods, are tied to adult outcomes (Elder, Johnson, & Crosnoe, 2003). Using a sample of 1,475 older adults, OLS regression analyses results did not statistically significantly link perceived family financial status in childhood and anxiety in older adults. Essay three employed a multinomial logistic regression model to analyze a temporal comparison theory approach (Albert, 1977) to changes in depressive symptomology. In a sample of 1,257 older adults, medium change in perceived relative income was not a significant predictor of change in depressive symptom trajectories. A second model showed that those with a very large downturn in perceived relative income were more likely (p < .01) to have a decrease in depressive symptoms and more likely (p < .10) to have an increase in depressive symptoms than to have no change. The analysis suggests that change in perceived relative income over time is consequential only if the change is both big and negative. Even then, the large shift could have different outcomes for different individuals. Overall, only limited support was found in the third paper supporting the influence of changes in perceived relative income on depressive symptom trajectories in older adults. The three studies and theoretical perspectives, however, point to the possibilities in future research. Who people use as their referent others is not yet clear, nor is whether personality traits, younger age, or individual histories, are a part of the equation that may connect perceived relative income or financial status to well-being measures.
Keywords: Older adults; Perceived relative income; Financial status; Well-being; Comparisons; Perceptions